Multiple sclerosis patients treated with intramuscular IFN-β-1a autoinjector in a real-world setting: prospective evaluation of treatment persistence, adherence, quality of life and satisfaction. (January 2015) - Hupperts, Raymond; Becker, Veit; Friedrich, Janne; Gobbi, Claudio; Salgado, Antonio Vasco; Sperling, Bjørn; You, Xiaojun
<x xml:space="preserve">Abstract</x> Objectives: The 12-month observational PERSIST study (NCT01405872) evaluated adherence associated with the intramuscular IFNβ-1a (i.m. IFN-β-1a) autoinjector pen in multiple sclerosis (MS) patients. Methods: MS patients initiating i.m. IFN-β-1a autoinjector treatment were prospectively assessed for physician-reported persistence (percentage of patients remaining on therapy) and patient-reported outcomes, including adherence (percentage of unmissed injections), compliance (percentage of patients missing no injections), tolerability (injection-site reactions [ISRs] and pain) and satisfaction. Results: The intent-to-treat population included 232 patients; of the 188 physician-reported 12-month completers, 182 patients remained on treatment (96.8% persistence). Monthly compliance rates were 87.5 – 96.2%. Mean monthly pain scores were 1.5 – 1.8 (scale: 0 = 'no pain'; 10 = 'extremely painful'). At 12 months, 73.5% of respondents reported no ISRs, 94.9% were satisfied/very satisfied with the autoinjector and 88.2% found using the device easy/very easy. Injection fear, injection anxiety and need for injection assistance by caregivers decreased from the initial visit to 12 months. No new safety signals were observed. Conclusions: The autoinjector pen is associated with high levels of persistence, compliance, adherence, and satisfaction, little-to-no pain and low need for caregiver assistance. Although these data are limited by reliance on patient questionnaires and the absence of a direct comparator group, this treatment may reduce barriers to injection therapy, while supporting long-term MS management.